Por amor y coraje : mujeres en movimientos urbanos de la ciudad de México - Massolo, Alejandra (Book collections on Project MUSE., 1992)
"Compelling exploratory investigation of women settlers in poor neighborhoods and their participation in social struggles during 1970s. Contends that although women were often the heart of social movements, their role has seldom been studied. Provides basic historical and theoretical/feminist frameworks. Mostly discusses life histories of four women and their recollections of popular struggles in three central and peripheral neighborhoods"--Handbook of Latin American Studies, v. 57.